3x+13+6x-2=

Simple and best practice solution for 3x+13+6x-2= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+13+6x-2= equation:


Simplifying
3x + 13 + 6x + -2 = 0

Reorder the terms:
13 + -2 + 3x + 6x = 0

Combine like terms: 13 + -2 = 11
11 + 3x + 6x = 0

Combine like terms: 3x + 6x = 9x
11 + 9x = 0

Solving
11 + 9x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-11' to each side of the equation.
11 + -11 + 9x = 0 + -11

Combine like terms: 11 + -11 = 0
0 + 9x = 0 + -11
9x = 0 + -11

Combine like terms: 0 + -11 = -11
9x = -11

Divide each side by '9'.
x = -1.222222222

Simplifying
x = -1.222222222

See similar equations:

| 11x^4+51x^3+9x^2+7=0 | | -27=r/12=19 | | (3x+13)+(6x-2)=y | | 4x+26=17 | | 11x^4+51x^2+97x=0 | | 2x+2iy=14i | | 2/3y-6=18 | | -2x(0)+y=1 | | 2x+14=60 | | x^3-15x^2-19x+70=0 | | (-1/8y^8)(1/8y^4) | | 2m-11m=81 | | 0.4x+2x=1.2 | | x^3+15x^2+19x-70=0 | | (4x^3-144x)/5= | | x-6=-2-3*6 | | 4x+11=-9x-18 | | 8y-3y-11=70.65 | | 4f+6(4f-3)=4(8f+4)-4 | | (k/5)-13=4 | | c^2-2c-120= | | 5/12-5/6 | | z/5-6=1/3/8 | | (-9p)-15=93 | | 550w=4500+200w | | 0.75x+6=0.5x+10 | | 2x+(-6)=414+6istheyareequvalent | | 13+5(6h+19)=17h+2h-13 | | -200+5.50x= | | 3x+4iy=9+8i | | 1=11x^2+10 | | f(x)=3x^2+48x+189 |

Equations solver categories